Application of Sequencing Batch Biofilm Reactor (SBBR) Using Microalgae Chorella sp. to Removal Nutrient in Grey Water - Shinta Elystia; Rika Kristin; David Andrio (Jurnal Teknik Kimia dan Lingkungan, 2023)
Grey water contains organic matter that is directly disposed to the environment without any treatment previously, will cause pollution and impacting life in the water. Treatment that can be done is using microorganisms. One of its kind is the microalgae Chlorella sp. which utilizes organic matter as a source of nutrients for its growth. In this study, the Kaldness 1 (K1) bio carrier was added as a medium for attaching microorganisms using the Sequencing Batch Biofilm Reactor (SBBR) process. The research objectives were (1) to know the maximum number of Chlorella sp. both attached and suspended in the Sequencing Batch Biofilm Reactor (SBBR), (2) to obtain the best cycle time and stabilization time in the removal of COD, Ammonia, and MLSS in grey water. The research was conducted by varying the stabilization time (1.5; 2 and 2.5 hours) in each cycle for four cycles with a constant variation of charging time 30 minutes, reaction 120 minutes, 45 minutes, separation 45 minutes, and carried out with four cycles, stirring speed at 60 rpm, the concentration of algae suspension in SBBR was 25% and the volume of Kaldness K1 medium was 20%. The results showed the number of microalgae cells Chlorella sp. was suspended and attached to 1.85 x 106 and 1.46 x 106 cells/ml. The best removal of COD, ammonia, and MLSS was found in the stabilization time variation of 1.5 hours in 4 cycles with a removal efficiency of 84% and 76%, respectively, and an increase in the concentration of suspended and attached MLSS by 4780 mg/l and 4720 mg/l. It can be concluded that the faster stabilization time, the more removal efficient will be.